The Provision of Accounting and Financial Support for BUMDes - Zuana, Muhammad Mujtaba Mitra; Ibad, Mohammad Sobarul (Sahwahita: Community Engagement Journal, 2023)
Bunutin Village is situated inside the administrative boundaries of Bangli District, which is located in the regency of Bangli. The implementation of this PKM holds significant importance due to the various challenges encountered by BUMDes Panca Sedana Sari Bunutin. These challenges encompass human resources, company type, capital, professionalism, community support and trust, as well as planning. The implementation of BUMDes aims to foster collaboration among community institutions, leading to enhanced effectiveness in promoting equitable community welfare. The establishment of BUMDes is predicated upon the assessment of the village's needs and potential, with the aim of enhancing the welfare of the community. Hence, it is imperative to implement substantial measures in order to ensure the effective, efficient, professional, and autonomous management of BUMDes. The process of generating financial reports for every company, including BUMDes, necessitates diligent execution. Financial reports play a crucial role in assessing the financial standing and operational effectiveness of a corporate entity. The financial reports now utilised employ a manual system and do not adhere to the prescribed financial accounting standards. One potential solution to address this issue is to provide training to managers on the utilisation of computer-based accounting programmes. The current state of business management is deemed insufficient, necessitating the provision of comprehensive education on the subject. This will enable individuals to effectively harness the potential of their communities. Based on the findings obtained from the service conducted on May 17, 2023, which was attended by all BUMDes (Village-Owned Enterprises) across the Bangli district, it was observed that a significant number of BUMDes administrators had not submitted financial reports for their business activities. This lack of reporting was attributed to a limited comprehension of accounting terminology and processes among the administrators. There are only 27 BUMDes (Village-Owned Enterprises) that have achieved development and possess the capability to generate financial reports and get comprehensive explanations pertaining to BUMDes accounting principles and financial guidance. The forthcoming year, the director of the Community and Village Empowerment service expresses the desire for Warmadewa University to sustain its current service while exploring alternative subject matters. Additionally, the director aims to provide more comprehensive guidance to BUMDes administrators in the meticulous preparation of financial reports.